Management of second-degree burn in child: A case report - Murastami, Ammarilis; Annisa Fildza Hashfi (Journal of Pakistan Association of Dermatologists, 2023)
Abstract Background: Burns are a common occurrence in children and are generally caused by scald. Burns can affect the socio-economic life and quality of life of the sufferer due to the disability that results in death. Second-degree burns have high enough morbidity and mortality that require adequate management. Management of burns in children includes assessment of the degree of burn, pain control, wound cleansing, debridement, appropriate dressing and wound evaluation. Method: A 5-year-old boy with the chief complaint of sores caused by scald on his chest, hands and feet. The area that was scalded with hot water immediately turned red, then blisters and accompanied by pain and chills. Examination of the dermatological status showed that the anterior trunk region showed hyperpigmented patches with multiple bullae with erosions in several parts. In the region of the antebrachialis et manus dextra et femoralis dextra, hyperpigmented patches appear with erosions. The patient was diagnosed with second-degree burns and received initial management in the form of fluid resuscitation, antibiotics and painkillers. Subsequent management with wound debridement in 3 sessions every 5 days, post-debridement silver sulfadiazine ointment, PRF in the 2nd and 3rd debridement sessions, mupirocin ointment post-debridement for deep erosions, 10% vitamin C solution in post-debridement medication, tretinoin 0.05% cream once a day at night, doxepin hydrogen chloride 5% cream applied twice a day, day and night, vaseline album is applied 2 times a day morning and evening as a home treatment. Result: The presence of bullae, lesions that appear wet and erythematous and also a history of contact with hot water, supports the diagnosis of second-degree burns. Initial management in this case aims to maintain hemostasis, namely by resuscitation of body fluids and control of pain and infection. Follow-up wound care consisted of wound cleansing, debridement, administration of topical agents to prevent infection and scarring and accelerate wound healing which included PRF, silver sulfadiazine ointment, 10% vitamin C solution, 0.05% tretinoin cream, 5% doxepin hydrogen chloride cream and vaseline album. The results after 8 weeks follow up showed improvement. Conclusion: Combination therapy of debridement, PRF, topical antibiotic, vitamin C solution, tretinoin cream, topical antihistamine, and vaseline album has been shown to improve second degree burn with minimal scarring. Keywords: child, debridement, burn injury, wound care